Development of a Novel Hybrid Thermoplastic Material and Holistic Assessment of Its Application Potential - Christos V. Katsiropoulos (MDPI AG, 2021)
Τhe development of a novel hybrid thermoplastic prepreg material enabling the fabrication of next-generation recyclable composite aerostructures produced by affordable, automated technologies is presented in the present work. The new hybrid material is produced using automated equipment designed and developed for this reason. A preliminary assessment of the application of the new material is made to obtain material properties related to its processability as well as to its strength. A typical aeronautical flat skin panel has been identified and produced using an autoclave-based process in order to assess the potential of the new material for producing aircraft structural parts. Moreover, a newly developed holistic index is implemented to enable a more holistic comparison of the suitability of the materials used for the panel production. The aspects considered for the material comparison are the quality, the environmental footprint, and the cost. The results of the study pointed out that the hybrid thermoplastic material that has been developed represents a viable manufacturing option from an industrial point of view and that its implementation in structural component manufacturing leads to clear cost and environmental advantages.